ANALYSIS OF THE PERFORMANCE EVALUATION OF THE LOGISTICS EXPRESS LINER PORT ON THE T-14 TANJUNG PERAK – LARANTUKA – LEWOLEBA – KALABAHI ROUTE IN REDUCING PRICE DISPARITY - Mawikere, William Aldrian Imanuel; Herijanto, Wahju (Journal of Civil Engineering, 2023)
The express liner program also known in Indonesia as "Tol Laut", initiated in 2015, aimed to reduce price disparities between Java and eastern Indonesian regions by providing regular and sustainable shipping services to remote areas. However, after seven years, the program has not significantly affected price disparities in eastern Indonesia. To evaluate the program's effectiveness, this study examined port performance and economic changes resulting from Sea Toll. The study identified areas of improvement for Larantuka, Lewoleba, and Kalabahi ports, such as docks, terminals, access roads, and storage facilities. Port performance evaluation revealed that Larantuka Port had subpar utilization of docks and stacking fields, while Lewoleba Port exhibited poor dock usage. Kalabahi Port, on the other hand, demonstrated good performance in dock utilization and stacking field usage. Regarding ship services, Larantuka Port showed good waiting time performance but poor loading and unloading productivity and ship effectiveness. Lewoleba Port had unfavorable waiting time in 2021 but improved in 2022, while its loading and unloading productivity and effectiveness were poor in both years. Kalabahi Port demonstrated good waiting time and effectiveness, but its loading and unloading productivity fell short of the standard. Evaluating the economic impact, the Sea Toll program did not significantly reduce the prices of necessities. Certain commodities experienced price increases influenced by regional distances and price fluctuations in Surabaya. However, medium rice prices decreased significantly in Larantuka and Kalabahi, indicating a positive impact of the Sea Toll program in those areas.